Prospek Pengembangan Sorgum untuk Ketahanan Pangan dan Energi - M. Arsyad Biba (Iptek Tanaman Pangan, 2011)
Sorghum can be planted in dryer climate area and requires less inputs compare with other food crops. Grain sorghum as food has better nutrient content than that of maize or rice. Its biomass can be used as animal feed, and the sugar content on the stem can be processed to produce bioethanol. From one kg of grain sorghum can be converted into one liter of ethanol. Suitable sorghum variety may produce 2,577 l of ethanol per ha of crop. Ever increasing demand for oil as source of energy is estimated to reach 62.11 million KL in 2025, and about 6.2% is expected to be substituted by gasohol. To supply the 621 thousand kl of gasohol, it needs 18,633 ton grain sorghum to be harvested from aound 9,317 ha of sorghum crop.